Strategic positioning during set pieces for the CAMBADA soccer team - Amaral, Filipe Alves (2014)
Robotics studies the design, construction and use of machines and or agents designated by robots, to perform tasks with some level of complexity. Within this scienti c domain, the coordination in multi-robot systems has been receiving a special attention, deserving a prominent role in the robot soccer issues. The way that each team coordinates its robots individually and together in order to perform cooperative tasks is the base of its strategy and in large part dictates the success of the team in the game environment. CAMBADA (Cooperative Autonomous Mobile roBots with Advanced Distributed Architecture) is the robot soccer team of the University of Aveiro, which participates in the RoboCup Middle Size League. This team was created and developed by students and teachers belonging to the IEETA research unit and the DETI. The aim of this work is the improvement of the strategic positioning in the set pieces situations, thus making it more dynamic and easily adaptable to the di erent strategies used by the opponent teams. The various changes made to existing algorithms, as well as new conditions included and their applicability are described throughout this dissertation. The work developed has been tested in the laboratory and used in robots in the Robótica 2014 competition. Although the development had not yet been fully completed by the date of the competition, it is important to emphasize the increased e cacy observed in team strategy in situations of set pieces, making the team more competitive and able to defend and attack better.